Development of Electrolyte and Nonelectrolyte E-Modules Integrated Demonstration Video and Science Literacy - Annisa Aulia; Hardeli Hardeli (Journal of Educational Chemistry (JEC), 2022)
The type of research used is Educational Design Research with the Plomp development model. The Plomp development model consists of 3 stages, namely; the preliminary research, the prototype phase, and the assessment phase. The research instruments used are; student observation sheets, teacher interview sheets, validity questionnaire sheets, practicality questionnaire sheets, and student learning outcomes tests. The e-module was validated by 5 validators. The results of the e-module validity test were analyzed using the Aiken's V formula, while the practicality test results were analyzed using a Likert scale. The results of the validity of the e-module obtained an average Aiken's V of 0.85 with a valid category and has a CVR value of 1  with a valid category. The results of the practicality of the e-module by teachers and students obtained an average practicality value of 98% and 84% with a very practical practicality category. The results of the e-module effectiveness test obtained an average N-Gain value for the experimental class of 0.63 with a medium category. Based on the research results, it can be concluded that the problem-based learning e-module electrolyte and nonelectrolyte solution integrated demonstration video and scientific literacy that has been developed is valid, practical, and effective.